Amyv asked in Science & MathematicsAgriculture · 8 years ago

# 5-(t+3)=-1+1t-6 Algebra?

I got t=9 -_-

Relevance
• 8 years ago

t = 4.5

you got t=9 because you forgot to divide the 9 by 2 in the end like so:

5 - (t+3) = -1 + t - 6

5 - t - 3 = -7 + t

5 - 3 + 7 = t + t

9 = 2t

9/2 = 2t/2

4.5 = t

• 8 years ago

I have no idea why this is in the agriculture section O_o

5-(t+3)=-1+1t-6

5 - t - 3 = -1 + t - 6

2 - t = -7 + t

2 = -7 +2t

2t = 9

t = 9/2 or 4.5

To check, you plug 4.5 back in for t to check if both sides come out the same and they both equal -2.5 which means your t is correct.

• 8 years ago

Well the actual problem would be. 5-1(t+3)=-1+1t-6 because theres an automatic understood one between the minus(or negative sign) and the parenthesis. To get the answer you'd have to do -1 times t and times positive 3 in order to get 5-1t-3=1+1t-6. Then you'll combine your alike terms in order to get 2-1t=-5+1t. From there you'll add 5 to both sides because it's a negative and you have to do the opposite of the actual sign. When you add your 5 to both sides you should get 7-1t=1t. From there you should and your -1t to both sides and that'll equal 7=2t. Divide 2 into 2t and the 7. Your answer should be 3 1/2 or 3.5.

Source(s): Brain. Good Algebra teacher.
• 8 years ago

this is what I got buddy,

5+1+6=(t+3)+1t

12=t+3+t

12-3=t+t

9=2t

9/2=2t/2

4.5=t